2019
DOI: 10.1002/bies.201900126
|View full text |Cite
|
Sign up to set email alerts
|

Can Designer Indels Be Tailored by Gene Editing?

Abstract: Genome editing with engineered nucleases (GEENs) introduce site-specific DNA double-strand breaks (DSBs) and repairs DSBs via nonhomologous end-joining (NHEJ) pathways that eventually create indels (insertions/ deletions) in a genome. Whether the features of indels resulting from gene editing could be customized is asked. A review of the literature reveals how gene editing technologies via NHEJ pathways impact gene editing. The survey consolidates a body of literature that suggests that the type (insertion, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…CRISPR-Cas9 has a repair profile closer to the environmental DSB's one compared to other nucleases with a high frequency of insertions of one nucleotide (Trimidal et al, 2019) and mainly repairs using out-of-frame indels (>70%) and microhomologies (Guo et al, 2018;Taheri-Ghahfarokhi et al, 2018).…”
Section: Repair Pathwaysmentioning
confidence: 99%
“…CRISPR-Cas9 has a repair profile closer to the environmental DSB's one compared to other nucleases with a high frequency of insertions of one nucleotide (Trimidal et al, 2019) and mainly repairs using out-of-frame indels (>70%) and microhomologies (Guo et al, 2018;Taheri-Ghahfarokhi et al, 2018).…”
Section: Repair Pathwaysmentioning
confidence: 99%
“…Our earlier in silico analysis showed that the gene editing enzymes likely interfere with binding of key components of DNA repair complexes and may alter the preference for C-NHEJ or A-NHEJ 10 . Although XRCC4 and MRE-11 are well studied NHEJ complex proteins, we investigated changes in cellular responses when both C-NHEJ and A-NHEJ are blocked by targeting these proteins.…”
Section: Introductionmentioning
confidence: 99%